La dinámica supranacional e intergubernamental aplicada en la Unión Europea tras las crisis de refugiados - Ricaurte Argoti, Maria Antonieta (2017)
This essay will further explore the dynamics between supranationalism and intergovernmentalism in the European Union in relation to a crisis. To this end, an influential issue will be analyzed, such as the refugee crisis. This case will be studied from a neo-functionalist perspective, in order to determine a greater inclination or not on the part of the Member States to act based on the defense of their sovereignty and how to do so this idea of supranationality begins to fade all this seen as a Back to the "spill-over" of integration. Following the analysis of this case, as well as four specific actions taken against it, it was found that, although there is a dynamic between both theories, supranationalism continues to predominate and continues its way to greater integration, although, there are demonstrations of the States Members with an intergovernmental dye due to periods of instability.